2013
DOI: 10.1051/0004-6361/201220540
|View full text |Cite
|
Sign up to set email alerts
|

Milky Way mass models for orbit calculations

Abstract: Context. Studying the trajectories of objects like stars, globular clusters, or satellite galaxies in the Milky Way allows the dark matter halo to be traced but requires reliable models of its gravitational potential. Aims. Realistic, yet simple and fully analytical, models have already been presented in the past. However, improved, as well as new, observational constraints have become available in the meantime, calling for a recalibration of the respective model parameters. Methods. Three widely used model po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
339
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(348 citation statements)
references
References 58 publications
6
339
0
Order By: Relevance
“…Our study is based on the best available data in the pre-Gaia era, mainly from the HIP2 (van Leeuwen 2011) and XHIP (Anderson & Francis 2012) catalogues. We used a numerical integration in the rectilinear, Galactocentric coordinates taking into account the full gravitational potential of the Galaxy in its modern shape (Irrgang et al 2013). For the main purpose (the accuracy assessment) we utilised covariance matrices of astrometric data which is included in the HIP2 catalogue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is based on the best available data in the pre-Gaia era, mainly from the HIP2 (van Leeuwen 2011) and XHIP (Anderson & Francis 2012) catalogues. We used a numerical integration in the rectilinear, Galactocentric coordinates taking into account the full gravitational potential of the Galaxy in its modern shape (Irrgang et al 2013). For the main purpose (the accuracy assessment) we utilised covariance matrices of astrometric data which is included in the HIP2 catalogue.…”
Section: Resultsmentioning
confidence: 99%
“…Numerical parameters for this model are taken from Irrgang et al (2013) and are summarised in Table 1. Since we always numerically integrate these equations simultaneously for a star and the Sun (to present final, heliocentric results), we also account for the gravitational attraction between these two bodies, as they can approach arbitrarily close. Our test calculation shows that the greatest influence of taking into account Sun-star gravitational interaction is for star HIP 26744.…”
Section: Galactic Motion Of Starsmentioning
confidence: 99%
“…Therefore, we do not expect the uncertainty in the Galactic potential to significant impact our findings. We use the three models presented in (Irrgang et al 2013), all of which fit the observed data well, to estimate that uncertainty in the 1 Under the most optimistic assumptions, H 1705-250 may have been born near its present location in (ρ, z), making a black-hole birth kick unnecessary; however this appears relatively unlikely given the present-day massive-star formation.…”
Section: Uncertainty In the Galactic Potentialmentioning
confidence: 99%
“…Data for the Milky GCs is from Georgiev et al (2009a), data for M31 is from Strader et al (2011) and data for GCs in local dwarf galaxies is from Georgiev et al (2009b). The mass model we use for the Milky way is from Irrgang et al (2013).…”
Section: Dynamical Evolution In Dwarf Galaxiesmentioning
confidence: 99%